Addiction psychiatry training experience, belief about addiction and brief screening for substance use among medical interns: A cross-sectional survey (Journal of Psychiatrists' Association of Nepal, 2019)
Introduction: Substance use and Substance Use Disorders (SUDs) have been shown to contribute substantially to the global burden of disease. However health workers belief system and attitude towards understanding and conceptualizing addiction makes the difference in the approach and treatment of the condition. This study tries to focus on the understanding and belief system of medical interns, and to see and contrast if their use of substance and their training about addiction during MBBS makes any difference in understanding and approaching addiction related cases.Material And Method: This is a cross- sectional, onetime assessment of medical interns working in KIST medical college and teaching hospital based on questionnaires and likert scale assessing addiction belief strength from time frame of April 2019 to 15th of May 2019. The sampling method will be convenient sampling method and finding will be evaluated further.Results: Out of 61 participants, 69% had completed psychiatry posting and were satisfied with their approach to patients with addiction related issues. Majority of them believed in disease model and their use of substance didn’t negatively influence the approach to patient care.Conclusion: Good exposure, training and skills given to students during MBBS years on addiction related diagnosis and treatment does help to understand addiction issues better and treat it as a biological model.